2000
DOI: 10.3758/bf03206927
|View full text |Cite
|
Sign up to set email alerts
|

Neural network models of categorical perception

Abstract: Studies of the categorical perception (CP) of sensory continua have a long and rich history in psychophysics. In 1977, Macmillan,Kaplan, and Creelman introduced the use of signal detection theory to CP studies. Anderson and colleagues simultaneously proposed the first neural model for CP, yet this line of research has been less well explored. In this paper, we assess the ability of neural-network models of CP to predict the psychophysical performance of real observers with speech sounds and artificial! novel s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 89 publications
1
61
0
Order By: Relevance
“…Other neural network models have also been proposed to show a biologically plausible mechanism by which these categorical perception effect could arise. Damper & Harnad (2000) trained both a Brain-State-In-A-Box (BSB) (following Anderson et al, 1977) and a back-propogation neural network model to show how categorical perception arises through spontaneous generation after training on two endpoint stimuli. They were able to produce typical categorical effects and reproduce the discrepancy between VOT boundaries between different places of articulation found in human participants.…”
Section: Models Of Categorical Effects In Consonant and Vowel Perceptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other neural network models have also been proposed to show a biologically plausible mechanism by which these categorical perception effect could arise. Damper & Harnad (2000) trained both a Brain-State-In-A-Box (BSB) (following Anderson et al, 1977) and a back-propogation neural network model to show how categorical perception arises through spontaneous generation after training on two endpoint stimuli. They were able to produce typical categorical effects and reproduce the discrepancy between VOT boundaries between different places of articulation found in human participants.…”
Section: Models Of Categorical Effects In Consonant and Vowel Perceptionmentioning
confidence: 99%
“…For stop consonants, the Liberman et al (1967) model comes close to predicting discrimination based on the identification function, while this prediction fails in vowel perception experiments. Neural network models have been applied to either vowel and liquid perception (Guenther and Gjaja, 1996; or to stop consonant perception (Damper & Harnad, 2000), but the same models have not typically been used to account for perception of both classes. While we now know that no phonemes are perceived purely categorically, the literature has nevertheless continued to treat strongly categorical perception as a separate phenomena from more continuous perception of other sounds, particularly vowels (Table 1).…”
Section: Common Ground In Vowel and Consonant Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…As explained in (Oudeyer, 2001a), this system contains neural maps which are similar to those used in (Guenther and Gjaja, 1996) and (Damper and Harnad, 2000). What is different is that on the one hand, motor and perceptual neural maps are coupled so that the learning of sounds affects the production of sounds, and on the other hand, these two other works used single agents that learnt an existing sound system, while here we use several agents that co-create a sound system.…”
Section: The Artificial Systemmentioning
confidence: 99%
“…While there are successful neural models of category learning (Gluck & Bower, 1988;Kruschke, 1992;Jäkel, Schölkopf, & Wichmann, 2008), one question that arises from selecting a neural model is whether it will be sufficient to allow a CP effect to be generated? Damper & Harnad (2000) conducted a systematic review and comparative experiments to determine if neural models are valid in such studies. They concluded that if categorization is in some way built into a sensory stimulus, "any general learning system operating on broadly neural principles ought to exhibit the essentials of CP" (p.862).…”
Section: Modeling Learned Categorical Perceptionmentioning
confidence: 99%